Structural monitoring using fiber optic sensors of a pre-stressed concrete viaduct during construction phases - Uva, Giuseppina; Porco, Francesco; Fiore, Andrea; Porco, Giacinto (Case studies in nondestructive testing and evaluation, 2014)
The paper presents a study about the monitoring of a pre-stressed reinforced concrete viaduct in Bari (Italy), by means of an optical fiber system embedded into the structural elements. The application case had two objectives: controlling the structural efficiency during the phases of construction, and allowing, in the future, the periodical check of the structural performance under service loads. Sensors were directly anchored to the prestressing strands during the manufacturing phases of the precast beams. By processing and analyzing the data acquired by the system during the different construction phases, it was possible to assess the strain variations related to load increments and stress losses, by comparing them with expected theoretical values. The specific case study shows that the availability of real-time monitoring procedures is nowadays a precious tool for checking the structural safety of critical facilities, in particular bridges.